Paracoccidioidomycosis in a child: exuberant presentation due to the inadvertent use of systemic corticosteroids - John Verrinder Veasey; Nabila Scabine Pessotti; Rute Facchini Lellis (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Paracoccidioidomycosis is a fungal infection that occurs in immunocompetent patients and are classified into two forms: the acute-subacute form, predominantly in young patients, and the chronic adult form that may present classic ulcerated lesions to rare sarcoid ones. We present the case of a boy whose infection began with sarcoid lesions but, after being mistakenly diagnosed with cutaneous sarcoidosis and treated (for three years) with prednisone, developed painful ulcerations throughout the body. After the correct diagnosis, with evidence of the fungus in histopathological and mycological examinations, the patient was properly treated with itraconazole for eight months and evolved with total remission of the disease.